Hippocampus-based contextual memory alters the morphological characteristics of astrocytes in the dentate gyrus. Issue 1 (December 2016) - Choi, Moonseok; Ahn, Sangzin; Yang, Eun-Jeong; Kim, Hyunju; Chong, Young Hae; Kim, Hye-Sun
Abstract Astrocytes have been reported to exist in two states, the resting and the reactive states. Morphological changes in the reactive state of astrocytes include an increase in thickness and number of processes, and an increase in the size of the cell body. Molecular changes also occur, such as an increase in the expression of glial fibrillary acidic protein (GFAP). However, the morphological and molecular changes during the process of learning and memory have not been elucidated. In the current study, we subjected Fvb/n mice to contextual fear conditioning, and checked for morphological and molecular changes in astrocytes. 1 h after fear conditioning, type II and type III astrocytes exhibited a unique status with an increased number of processes and decreased GFAP expression which differed from the typical resting or reactive state. In addition, the protein level of excitatory excitatory amino acid transporter 2 (EAAT2) was increased 1 h to 24 h after contextual fear conditioning while EAAT1 did not show any alterations. Connexin 43 (Cx43) protein was found to be increased at 24 h after fear conditioning. These data suggest that hippocampus-based contextual memory process induces changes in the status of astrocytes towards a novel status different from typical resting or reactive states. These morphological and molecular changes may be in line with functional changes.